2013
DOI: 10.1002/ajpa.22346
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for sex biases in milk macronutrients, energy, or breastfeeding frequency in a sample of filipino mothers

Abstract: Maternal reproductive investment includes both the energetic costs of gestation and lactation. For most humans, the metabolic costs of lactation will exceed those of gestation. Mothers must balance reproductive investment in any single offspring against future reproductive potential. Among mammals broadly, mothers may differentially invest in offspring based on sex and maternal condition provided such differences investment influence future offspring reproductive success. For humans, there has been considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…In addition, Fujita et al () observed that economically sufficient mothers in rural Kenya produced richer milk for sons than daughters while poor mothers produced richer milk for daughters than sons. Although these studies are consistent with the Trivers–Willard hypothesis, which predicts the unequal parental investment between males and females depending on maternal condition and offspring reproductive potential (Trivers and Willard, ), a recent study based on milk composition found no support for this hypothesis (Quinn, ). It must be noted that it is difficult to illustrate that energy savings a mother would gain by constraining the growth in 18 g (or less) would be sufficiently beneficial for this “strategy” to become genetically encoded and physiologically expressed as an adaptation, through evolutionary time.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, Fujita et al () observed that economically sufficient mothers in rural Kenya produced richer milk for sons than daughters while poor mothers produced richer milk for daughters than sons. Although these studies are consistent with the Trivers–Willard hypothesis, which predicts the unequal parental investment between males and females depending on maternal condition and offspring reproductive potential (Trivers and Willard, ), a recent study based on milk composition found no support for this hypothesis (Quinn, ). It must be noted that it is difficult to illustrate that energy savings a mother would gain by constraining the growth in 18 g (or less) would be sufficiently beneficial for this “strategy” to become genetically encoded and physiologically expressed as an adaptation, through evolutionary time.…”
Section: Discussionsupporting
confidence: 55%
“…In summary, natural biological processes in animals provide milk with distinctively different compositions to suit the nutritional needs based on the sex of the offspring. On the other hand, the available evidence of sex-specific differences in human milk composition are not well established [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Suckling behavior, however, is not useful for estimating milk energy transfer as verified by experimental use of radio-labeled isotopes in Equus caballus [22]. Direct evidence for sex-biased milk synthesis among nondomesticated species has now been reported in ungulates (Cervus elaphus hispanicus, [23]), rodents (Myodes glareolus [24]), primates (Macaca mulatta [25][26]; Homo sapiens [27][28][29], but see also [30] for exception), and marsupials (Macropus eugenii, [31]). Drawing systematic conclusions from the studies to date, however, is challenging in part because most have been limited by relatively small sample sizes or report milk composition without accounting for milk yield.…”
Section: Introductionmentioning
confidence: 99%